Reply to Comment by A. G. Davies on “Io Hot Spot Distribution Detected by Juno/JIRAM” - F. Zambon; A. Mura; F. Tosi (Geophysical Research Letters)
Abstract Zambon et al. (2023, https://doi.org/10.1029/2022gl100597) presented a catalog of Io hot spots based on JIRAM M‐band images acquired in Juno orbits 10 to 33. They identified 242 hot spots, including 23 not previously reported in other catalogs, observing a higher hot spot number density in the northern polar region. Davies (2024) disputes location and counting of part of these hot spots, attributing the differences between the Zambon et al. (2023, https://doi.org/10.1029/2022gl100597) results and those obtained by Davies et al. (2024, https://doi.org/10.1038/s41550‐023‐02123‐5) to a misregistration of the JIRAM images. Here we reply to Davies (2024) showing that discrepancies in the results are due to the different methodologies, assumptions, and goals considered in the two works.